Quality variation analysis and rehydration kinetics modeling of yuba subjecting to three different drying process - Jicai Bi; Junyang Zhang; Zhuo Chen; Yunbo Li; Mohammed Obadi; Wenhao Liu; Renbing Qin; Lingwen Zhang; Hongju He (Food Chemistry: X)
This study investigated the effects of hot air drying (HAD), microwave vacuum drying (MVD), and vacuum frying drying (VFD) on the quality of yuba and utilized mathematical models (Peleg model, Weibull model, first-order kinetic model, and exponential association model) to explore the rehydration kinetics of yuba. The results indicated that, compared to HAD, MVD significantly increased yuba's L* value and sensory score, while VFD notably reduced the cooking loss and enhanced moisture retention. Significant changes were observed in the texture of yuba before and after cooking, with distinct differences noted under microscopic observation, and a pronounced change in protein secondary structure. The Peleg model can effectively fit the rehydration processes of HAD and VFD yuba, while the first-order kinetic model can effectively fit the rehydration processes of MVD yuba. This study provides a valuable reference for yuba's drying methods and rehydration kinetics model.